Advertising and tobacco: effects in consume after the new Spanish law against tobacco - Rodríguez Martínez, M. (Revista Española de Comunicación en Salud, 2016)
Introduction. Advertising plays an important role in the change of the life style, above all teenagers. Tobacco was advertised until law 28/2005 appeared in Spain. Once this law was introduced, guided by Framework Convention on Tobacco Control, the attitude of the population about this habit is wanted to be known.Aims. Finding out the rate of tobacco adicction in Spain in 2006, just right after passing the banning tobacco advertising law.Material and methods. A review of the existing laws was carried out about tobacco advertising and by-products, and the prevalence of smoking was became known through the surveys from the Ministry of Health and Consumption in Spain.Results. With the disclosed data by the surveys, an important number of ex-smoker and an attitude of less smoking are shown. Discussion. The results are related to reduction of smokers and implantation of this law.Conclusions. Regulation efficiency and effectiveness, against tobacco epidemic, mainly in teenagers, are proved.